The structure of materials - Allen, Samuel M. 4 0 16; Thomas, Edwin L.; 5 (New York : Wiley, 1999)
Presents an introduction to the structure of materials, focusing on the three different states of solid, condensed matter, including glasses, crystals, and liquid crystals, and developing one set of tools for describing all of them. Includes charts, graphs, tables, and illustrations.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Materials science.;Crystallography.;Physical sciences.;Crystals.; 20; 2